The Impact of Internal Communication on Employee Engagement: The Example of Marketing Agencies - Blažević, Iva (Digital Repository of Theses, 2025)
Successful internal communication inside an organization or company is the main condition for the achievement of business goals given the fact that internal communication directly affects the satisfaction, motivation and engagement of employees. Well-organized internal communication channels ensure a quick and efficient information flow and based on those quick responses; job done. Employee engagement is becoming valuable as business success. In a modern work environment employee engagement represents vital element to take into consideration as a competitive advantage and value proposition when talking about a competent and successful organization or company. The concept of employee engagement is becoming increasingly popular around the world nowadays, and Croatia is no exception. Due to the direct connection with the company's goals, internal communication is the basis of every good organizational communication strategy. Communication is a key element for the growth and development of the organization or company and the success of management depends on communication with the employees. Every organization or company has its own internal communication structure which enables exchange ideas, mutual understanding, and the elimination of conflicts. This dissertation examines the impact of internal communication on employees’ engagement in marketing agencies by using the survey questionnaire. The outcome of this dissertation is meant to help marketing agencies, but also management of organizations and companies in general, better understand the situation, as well as the possible driving factors at the level of engagement. Empirical research was conducted on marketing agencies in Croatia, which included media buying, PR, full and creative agencies. The aim of research results had shown the existence of a clear link between internal communication and employee engagement, but also the fact that engaged employees work better and are more focused on performance and achievement of better business results. Empirical research was conducted on a research sample of 150 marketing agencies in Croatia and it could be stated that clear and transparent internal communication results in greater employee engagement who works better and are more focused on best performance and achieving better business results. Keywords: business communication; internal communication, management, employees’ engagement, marketing agencies